2022
DOI: 10.1021/acschemneuro.2c00057
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcase Inhibitor ASN90 is a Multimodal Drug Candidate for Tau and α-Synuclein Proteinopathies

Abstract: Neurodegenerative proteinopathies are characterized by the intracellular formation of insoluble and toxic protein aggregates in the brain that are closely linked to disease progression. In Alzheimer’s disease and in rare tauopathies, aggregation of the microtubule-associated tau protein leads to the formation of neurofibrillary tangles (NFT). In Parkinson’s disease (PD) and other α-synucleinopathies, intracellular Lewy bodies containing aggregates of α-synuclein constitute the pathological hallmark. Inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 66 publications
0
55
0
Order By: Relevance
“…We recently shown the efficiency of Thiamet-G to improve global O-GlcNAcylation levels and 5-FU response in murine carcinogen-induced CRC tumors (34). In addition, other selective OGA inhibitors, MK-8719 (143) and ASN120290 (previously known as ASN-561) (144) have obtained the orphan drug designation by the FDA for the treatment of the progressive supranuclear palsy (PSP) in 2016 and 2018 respectively. However, modulating global cellular O-GlcNAcylation levels have limits in term of therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…We recently shown the efficiency of Thiamet-G to improve global O-GlcNAcylation levels and 5-FU response in murine carcinogen-induced CRC tumors (34). In addition, other selective OGA inhibitors, MK-8719 (143) and ASN120290 (previously known as ASN-561) (144) have obtained the orphan drug designation by the FDA for the treatment of the progressive supranuclear palsy (PSP) in 2016 and 2018 respectively. However, modulating global cellular O-GlcNAcylation levels have limits in term of therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The serine and threonine sites of tau are also affected by O-GlcNAcylation, many known O-GlcNAcylation sites are nearby or found to be overlapping with phosphorylation sites, and thus it has been suggested that these two could regulate phosphorylation positively or negatively. For instance, the inhibition of glycoside hydrolase O-GlcNAcase halts the removal of O-GlcNAc moieties from intracellular proteins that prevent developing tau pathology [ 56 ]. Recently, Yin and colleagues’ study showed that SIRT1 member of Sirtuins, a family of signaling proteins, increases the protein level of O-GlcNAcase by C/enhancer binding protein(C/EBPα).…”
Section: Post-translational Modificationmentioning
confidence: 99%
“…To determine whether ASN90 promotes the O−GlcNAcylation of α‐synuclein in vivo , [39] the team employed a chemoenzymatic mass‐tagging method [47] that involves GalT‐mediated GalNAz labeling of native O−GlcNAc moieties on α‐synuclein, followed by a click reaction with dibenzocyclooctyne‐polyethylene glycol (PEG) probes [33] (Figure 2). In brain homogenates from PD mouse models, O−GlcNAcylated α‐synuclein tagged with the PEG probe resulted in a band (∼30 kDa) distinct from that of the unmodified protein (15 kDa) [39] . Using this assay, the team observed approximately 20% of total α‐synuclein modified by O−GlcNAc in vehicle‐treated controls, whereas chronic ASN90 treatment increased overall α‐synuclein O−GlcNAcylation by 1.5‐fold [39] .…”
Section: Oga Inhibitors As Drug Candidates For Human Neurodegenerationmentioning
confidence: 99%